The Influence of Chayote Juice Mix with Honey Pineapple “Lasinasdu” on Blood Pressure Changes Among Hypertension Patients - Luthfi Elia Rachmawati; Didit Damayanti; Sa’diah Multi Karina (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Hypertension is one of the risk factors that cause a total of 1.7 million (23,7%) deaths in Indonesia. The prevalence of hypertension in Indonesia is increasing every year. Based on literature, potassium from chayote and honey pineapple influence the renin-angiotensin system so that it can lower blood pressure. This study aims to analyze the effect of giving “Lasinasdu” honey pineapple chayote juice on blood pressure in patients with hypertension. The subjects of this study were women with prehypertension-hypertension aged 18-44 years chosen using purposive sampling. This study is a pre-experimental study with a one-group pretest-posttest approach with the intervention of giving honey pineapple chayote juice. . The intervention in the form of giving honey pineapple chayote juice given as much as 250 ml for 5 days was tested with the Wilcoxon test showed the result that there was an effect of the intervention of giving “Lasinasdu” honey pineapple chayote juice to changes in systolic blood pressure significantly (p = 0.000) and there was no effect of the intervention of “Lasinasdu” honey pineapple chayote juice on changes in diastolic blood pressure (p = 0.059). Consumption of “Lasinasdu” juice can be used as a non-pharmacological alternative to prevent or treat hypertension.